Physico-chemical parameter correlations in the [RuCl2(CO)(L)(PPh3)2] complexes (L = N-heterocycles) - Wohnrath, Karen; Batista, Alzir A.; Ferreira, Antonio Gilberto; Zukerman-Schpector, Julio; Oliveira, Luiz Antonio A. de [UNESP]; Castellano, Eduardo E. (My University, 1998)
Fourteen complexes in the series [RuCl2(CO)(L)(PPh3)2] (where L = N-heterocycles) have been prepared and characterized by IR and NMR spectroscopies, and cyclic voltammetry. A good correlation is found between observed and calculated electrochemical potentials; E1/2 vs pKa or (Gp, σm for a series of similar ligands. It is now reported that the carbonyl stretching frequency, νCO, and the 13C and 31P NMR signals do not correlate well with any of the physico-chemical parameters used (E1/2, Taft's and Hammett's parameters). This behaviour is probably due to the characteristics of the Ru(II) species, which does not transmit the steric and electron donor/acceptor properties of the ligands to the carbonyl group, or because the measurements are not able to detect the effect induced by the changes in the ligand L. Indeed, good correlations are obtained when the measurements directly involve the metal centre, as is the case in the E1/2 measurements. Crystals of o[RuCl2(CO)(4-pic)(PPh3)2] are monoclinic, space group P21/n, a = 12.019(2), b = 13.825(3) and c = 22.253(3) . The structure was solved by the Patterson method and was refined by full-matrix least-squares procedure to R = 0.054 and Rw = 0.055, for 2114 reflections with I > 3σ(I). For L = 2-acetylpyridine and 2-methylimidazole, complexes with formulae [RuCl2(CO)(L)(PPh3)] · L and [RuCl2(CO)(L)2 (PPh3)], respectively, were obtained. © 1998 Elsevier Science Ltd. All rights reserved.
Keywords: Lever's parameters; Ruthenium; X-ray structure